2022
DOI: 10.1101/2022.10.21.512844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene Gain and Loss from the Asian Corn Borer W Chromosome

Abstract: We built a chromosome-level genome assembly of the Asian corn borer,Ostrinia furnacalisGuenée (Lepidoptera: Pyralidae, Pyraloidea), an economically important pest in corn, from a female, including both the Z and W chromosome. Despite deep conservation of the Z chromosome across Lepidoptera, our chromosome-level W assembly reveals this chromosome has recently derived from theO. furnicalisZ chromosome. We also recover evidence for convergent formation of the W in two other related families, all independently der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 86 publications
1
9
2
Order By: Relevance
“…Using homology tests between the W and remaining 31 chromosomes in H. misippus and other Lepidoptera we show that there is a degree of similarity between the W and the Z chromosome, suggesting a possible common origin. These results differ from the homology tests performed in Danaus plexipuss (Lewis et al 2021), Kallima inachus (Yang et al 2020) and Dryas iulia (Lewis et al 2021), where no similarity was found between the W and the Z chromosome and are more in line with results in the Asian corn borer, Ostrinia furnacalis, a moth belonging to the Pyraloidea, which suggests a common autosomal origin of the Z and the W chromosome (Dai et al 2022). Contrastingly, the lack of similarity between the W and the Z in five of the seven species studied could suggest a B chromosome origin or could be the result of the rapid evolution of the W, which could be interfering with the inference of homology (Yoshido et al 2013;Vítková et al 2007).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Using homology tests between the W and remaining 31 chromosomes in H. misippus and other Lepidoptera we show that there is a degree of similarity between the W and the Z chromosome, suggesting a possible common origin. These results differ from the homology tests performed in Danaus plexipuss (Lewis et al 2021), Kallima inachus (Yang et al 2020) and Dryas iulia (Lewis et al 2021), where no similarity was found between the W and the Z chromosome and are more in line with results in the Asian corn borer, Ostrinia furnacalis, a moth belonging to the Pyraloidea, which suggests a common autosomal origin of the Z and the W chromosome (Dai et al 2022). Contrastingly, the lack of similarity between the W and the Z in five of the seven species studied could suggest a B chromosome origin or could be the result of the rapid evolution of the W, which could be interfering with the inference of homology (Yoshido et al 2013;Vítková et al 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, and irrespective of the specific origin, the number of evolutionary events leading to the formation of the W chromosome has also been debated. That is whether all W chromosomes in the Lepidoptera share a common evolutionary origin of if their inception was the result of multiple independent events, with the most recent evidence supporting the latter (Dai et al 2022;Lewis et al 2021)(Figure 1D-E). hypothesis is that the W chromosome evolved from a B chromosome, which are non-essential chromosomes that vary in number in populations and species.…”
Section: Introductionmentioning
confidence: 99%
“…1). This view aligns with evidence of a key role of major rearrangements in the evolution of sex chromosomes in other advanced Lepidoptera (Smith et al 2016;Mongue et al 2017;Carabajal-Paladino et al 2019;Hill et al 2019;Yoshido et al 2005Yoshido et al , 2020Hejnickova et al 2021), and with the recent demonstration of a shared Z-origin of the W chromosomes in two species of Crambidae (also advanced Lepidoptera) (Dai et al 2022).…”
Section: Discussionsupporting
confidence: 86%
“…Our data further support the notion that W chromosome evolution is extraordinarily rapid (Vitkova et al 2007; Sahara et al 2012; Hejnickova et al 2021). The evolution of lepidopteran W chromosomes frequently involves sequence deletions, the incorporation of autosomal segments, and extensive sequence multiplication (Abe et al 2005a, 2005b; Traut et al 2013; Lewis et al 2021; Dai et al 2022). Our identification of autosomal segments copied into and expanding on the W chromosome in P. mannii exemplifies some of these processes.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that Pelw30 is a neo-chromosome or W sex chromosome. Specifically, the high content of repetitive sequences in Pelw30 is particularly similar to that of the W sex chromosome [ 25 , 27 , 81 ], but there is no clear evidence for this at present. Chromosome 15 of P. machaon (Pmac15) was collinear to chromosomes 15 (Pelw15) and 28 (Pelw28) of P. elwesi .…”
Section: Resultsmentioning
confidence: 99%